நிறுவுக: \(\frac { \tan { \theta } +\sec { \theta } -1 }{ \tan { \theta } -\sec { \theta } +1 } =\frac { 1+\sin { \theta } }{ \cos { \theta } } \)

Searching in 10,00,000 questions...
நிறுவுக: \(\frac { \tan { \theta } +\sec { \theta } -1 }{ \tan { \theta } -\sec { \theta } +1 } =\frac { 1+\sin { \theta } }{ \cos { \theta } } \)
\(\frac { \tan { \theta } +\sec { \theta } -1 }{ \tan { \theta } -\sec { \theta } +1 } =\frac { \tan { \theta } +\sec { \theta } -\left( \sec ^{ 2 }{ \theta } -\tan ^{ 2 }{ \theta } \right) }{ \tan { \theta } -\sec { \theta } +1 } \)
\(=\frac { \left( \tan { \theta } +\sec { \theta } \right) \left( 1-\left( \sec { \theta } -\tan { \theta } \right) \right) }{ \tan { \theta } -\sec { \theta } +1 } \)
\(=\tan { \theta } +\sec { \theta } =\frac { 1+\sin { \theta } }{ \cos { \theta } } \)
நிறுவுக: \(\frac { \tan { \theta } +\sec { \theta } -1 }{ \tan { \theta } -\sec { \theta } +1 } =\frac { 1+\sin { \theta } }{ \cos { \theta } } \)